On the Occasion of the 30th Anniversary of the Restoration of Serbia-Israel Relations - Nikolić, Aleksandar (Napredak, 2022)
The position of the Jewish community members during the decades of the restoration of Serbian statehood, as well as the states constituted by the Serbian people,experienced ups and downs.The festive occasion of the 30th anniversary of the renewal of diplomatic relations between the Republic of Serbia and the State of Israel points to the evocation of subtly emotional peculiarities in their most picturesque form.The protagonists include the most successful rulers of two Serbian dynasties – Prince Miloš Obrenović and King Peter I Karađorđević the Liberator. This article is a reflection in honour of two selected features: the founder of Serbian civic music culture, Josif Šlezinger, and the active and public promotional participation of King Peter the First in laying the foundation stone and of the Belgrade synagogue Beth Yisrael and its consecration the following year. With its purposefully modest volume,the review looks at the fascinating adaptability of the Jewish community, which is rapidly turning into one of the most constructive factors in including the country in European socio-economic flows, on the one hand, as well as the process anticipation by national leaders who have left an indelible mark in the history of their people and the region,on the other hand.